Firm's survival, rating and efficiency: new empirical evidence. Issue 6 (10th July 2017) - Manello, Alessandro; Calabrese, Giuseppe Giulio
Abstract : Purpose: The purpose of this paper is to investigate the determinants of firms' survival during crisis in the Italian automotive value chain. Design/methodology/approach: The authors propose a survival analysis, based on a dichotomic model, in which supply chain features, technical efficiency (TE) and ratings are included as explanatory variables with other controls. Findings: TE and financial health positively influence survival. Some supply chain variables are significant such as direct supply, geographical location and outsourcing level, whereas the proximity to the national carmaker is insignificant. Research limitations/implications: The main limitation of the study is the lack of qualitative data related to supply management practice in the automotive industry. Originality/value: The study combine supply chain aspects with firms' survival, TE and financial ratings.